Determination of immune response against alum-precipitated fowl cholera vaccine in the quail, Coturnix japonica (University Journal of Zoology, Rajshahi University, 2012)
The immune response of a formalin-inactivated alum-precipitated fowl cholera vaccine (FCV) was evaluated in quails, Coturnix japonica (Order: Galliformes and Family: Mimidae). All quails, irrespective of sex and 8-weeks-old were immunized with 5×107CFU/ml/quail subcutaneously (SC) and intramuscularly (IM). A Booster immunization was given with similar dose and routes at 15 days after primary immunization in groups A and B while group C served as unimmunized control. Pre-immunized sera were collected from all groups of birds to assay the primary antibody levels in them. Sera of the immunized and control quails were collected at 15 and 30 days post immunization. The degree of immunity produced in each group of quails following primary and secondary immunizations were determined by measuring their serum antibody titres using passive haemagglutination assay (PHA) test. The level of antibody was significantly increased both primary and booster immunization in immunized quails as determined by PHA titres. Two weeks after final immunization, the quails were challenged with a virulent isolate of fowl cholera and immunized quails conferred 100% protection while all the control quails were dead within 10 days post challenge.   Key words: Fowl cholera; alum-precipitated vaccine; immune response; PHA test; quail DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9467 UJZRU 2010; 29(1): 57-59